2017
DOI: 10.3389/fpsyg.2017.00786
|View full text |Cite
|
Sign up to set email alerts
|

New Strategies in the New Millennium: Servant Leadership As Enhancer of Service Climate and Customer Service Performance

Abstract: In a world in which customers are increasingly looking for solutions to their own concerns on how to make a better globalized world, new organizational strategies are emerging to approach the customer in the current third millennium. Servant leadership, which involves putting employees’ needs first and serving the broader society, is emerging as a new strategic mechanism to approach the customer in line with the new social values-driven Marketing 3.0 era. Yet research has ignored the role and the various mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 104 publications
0
14
0
Order By: Relevance
“…Moreover, Russell and Stone (2002) highlight the importance of servant leadership for improving organisational performance because it creates a sort of organisational culture in which followers demonstrate positive behaviours and attitudes. Other empirical evidence found that servant leadership is positively associated with employee voice behaviour (Chughtai, 2016;Lapointe and Vandenberghe, 2018), thriving at work (Walumbwa et al, 2018), employee creativity (Yang et al, 2017), job performance (Schwarz et al, 2016), employee organisational citizenship behaviour (Amah, 2018) and group social capital (Linuesa-Langreo et al, 2017) . These empirical results are in line with the social exchange theory (Blau, 1964), which explains the mechanism through which servant leadership stimulates positive attitudes and behaviours at the workplace.…”
Section: Servant Leadershipmentioning
confidence: 99%
“…Moreover, Russell and Stone (2002) highlight the importance of servant leadership for improving organisational performance because it creates a sort of organisational culture in which followers demonstrate positive behaviours and attitudes. Other empirical evidence found that servant leadership is positively associated with employee voice behaviour (Chughtai, 2016;Lapointe and Vandenberghe, 2018), thriving at work (Walumbwa et al, 2018), employee creativity (Yang et al, 2017), job performance (Schwarz et al, 2016), employee organisational citizenship behaviour (Amah, 2018) and group social capital (Linuesa-Langreo et al, 2017) . These empirical results are in line with the social exchange theory (Blau, 1964), which explains the mechanism through which servant leadership stimulates positive attitudes and behaviours at the workplace.…”
Section: Servant Leadershipmentioning
confidence: 99%
“…Broadcasters with the characteristics of service leadership are good at showing empathy by listening to and understanding the feelings and needs of others ( Spears and Lawrence, 2002 ). They adopt the psychological perspective of their followers and show warmth, compassion, and forgiveness in their relationships, a trait that helps create a brotherly, compassionate, and trusting atmosphere ( Van Dierendonck and Nuijten, 2011 ; Linuesa-Langreo et al, 2017 ). This enables a dependent audience to obtain a sense of belonging ( Singelis, 1994 ) and thus to hold a positive attitude toward the service broadcaster.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Evidence linking servant leadership with service climate provides support for servant leadership’s task-oriented focus. Service climate mediated the link between servant leadership and task-focused outcomes such as unit sales (Hunter et al, 2013), unit customer service performance (Linuesa-Langreo et al, 2017), and firm performance (Huang et al, 2016). In sum, servant leaders model task-relevant skills that convey normative behavioral expectations as well as motivate and equip followers to reach unit goals.…”
Section: Hypothesesmentioning
confidence: 99%